New hierarchical approach to reactive routing protocols for wireless ad hoc networks with cross-layer design. (7th December 2006) - Tarique, Mohammed; Tepe, Kemal E.
A hierarchical routing protocol is designed for reactive ad hoc networks. In the hierarchical architectures network nodes are classified as Mobile Nodes (MNs) and Forwarding Nodes (FNs). FNs are selected from MNs during the route discovery phase of the reactive routing. This FN selection algorithm is distributed, dynamic and requires no additional protocol messaging other than used during the route discovery. The FN selection algorithm is further improved by using network congestion information from Medium Access (MAC) layer. The protocol is implemented using Dynamic Source Routing (DSR) protocol, and the new protocol is called HDSR. Simulation results show that HDSR significantly improves the routing efficiency in wireless ad hoc networks.